The Relationship Between Teacher Certification and Work Motivation on Teacher Performance - Murnia, Murnia; Fitria, Happy; Mulyadi, Mulyadi (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
To achieve the goals and objectives of education, namely educating the nation's life and developing a complete human being who believes and is devoted to God Almighty and virtuous, has knowledge and skills, physical and spiritual health, a steady and independent personality and a sense of community and national responsibility. This study aims to analyse (1) The effect of teacher certification on the performance of public junior high school teachers in Air Kumbang District, (2) The effect of teacher work motivation on teacher performance and (3) The effect of teacher certification and teacher work motivation on teacher performance. This study used quantitative descriptive methods and used questionnaires as research instruments. Data was collected from 33 teachers who had been certified by public junior high schools in Air Kumbang sub-district. The collected data is then analysed by multiple regression analysis methods with a Quantitative approach. It can be concluded that the significance value for the effect of teacher certification (X1) and work motivation (X2) on teacher performance (Y) is 0.019 < 0.05 and 0.037 < 0.05. Then > are 6.113> 3.32, and 4.775> 3.32. This proves that Ho3 is rejected and Ha3 is accepted. This means that there is a significant effect of teacher certification (X1) and work motivation (X2) on teacher performance (Y).